Brief Report: Virologic Response by Baseline Viral Load With Dolutegravir Plus Lamivudine vs Dolutegravir Plus Tenofovir Disoproxil Fumarate/Emtricitabine. (1st May 2020) - Eron, Joseph; Hung, Chien-Ching; Baril, Jean-Guy; Slim, Jihad; Falcó, Vicenç; Bogner, Johannes; Maggiolo, Franco; Mills, Anthony; Sievers, Jörg; Man, Choy Y.; Urbaityte, Rimgaile; Underwood, Mark; et al.
Abstract : Background: To investigate antiviral potency of the 2-drug regimen (2DR) dolutegravir plus lamivudine vs the 3-drug regimen (3DR) dolutegravir plus tenofovir disoproxil fumarate/emtricitabine, we performed a post-hoc analysis assessing antiviral response rates in the phase III GEMINI-1 and GEMINI-2 studies by baseline viral load (VL). Setting: One hundred ninety-two centers in 21 countries. Methods: Treatment-naive HIV-1–infected participants with screening VL ⩽500, 000 copies/mL were randomized 1:1 to once-daily dolutegravir plus lamivudine or dolutegravir plus tenofovir disoproxil fumarate/emtricitabine. Median change from baseline was determined for log10 -transformed VL in the overall study population and the subpopulation with baseline VL >100, 000 copies/mL. Proportion of participants achieving plasma VL <50 copies/mL (Snapshot algorithm) or <40 copies/mL (Abbott RealTime HIV-1 assay) and target not detected was assessed through week 48 by baseline VL. Time to viral suppression was determined (nonparametric Kaplan–Meier method). Results: For 293 participants with baseline VL >100, 000 copies/mL, median change from baseline at week 4 was −3.38 and −3.40 log10 copies/mL in the 2DR and 3DR groups, respectively; reduction was sustained throughout 48 weeks. Time to VL <50 copies/mL was longer in participants with baseline VL >100, 000 copies/mL than the overall study population (57 [week 8] vs 29 days [week 4]) and similar between the 2DR and 3DR groups. Proportion of participants with VL <50 or <40 copies/mL and target not detected was similar between groups, irrespective of baseline VL, at all tested visits throughout 48 weeks. Conclusion: Dolutegravir plus lamivudine demonstrates high antiviral potency in treatment-naive HIV-1–infected individuals across baseline VL strata.